Mixed-monolayer glyconanoparticles for the detection of cholera toxin by surface enhanced Raman spectroscopy. Issue 1 (9th December 2015) - Simpson, Jonathan; Craig, Derek; Faulds, Karen; Graham, Duncan
Abstract : Cholera toxin B subunit (CTB) is detected sensitively in samples of synthetic freshwater by measuring changes in the SERS intensity of the glyconanoparticles upon their binding of CTB and subsequently aggregating. The particles are coated in both galactose and sialic acid. Abstract : We have produced silver glyconanoparticles for the sensitive (56 ng mL −1 ), low volume and rapid detection of cholera toxin B-subunit (CTB) in synthetic freshwater (simulating the ion compositions of natural waters in which CTB could be found). This is achieved by monitoring the changes in surface enhanced Raman scattering (SERS) intensity of a Raman reporter bound to the glyconanoparticle surface. The particles selectively aggregate upon interaction with CTB, causing an increase in the measured SERS signal. The particles are designed to mimic the interactions involving the cell surface GM1 ganglioside and CTB. This is achieved by using a combination of polyethylene glycol linkers terminated with either galactose or sialic acid.